“ANTESEDEN GOOD CORPORATE GOVERNANCE DAN KONSEKUENSINYA TERHADAP MANAJEMEN LABA PADA PERUSAHAAN YANG TERDAFTAR DALAM CORPORATE GOVERNANCE PERCEPTION INDEX” - Vitara Arta Ciputri, 14.05.52.0167; Widiatmoko, Jacobus (Students' Journal of Accounting and Banking, 2018)
This study is examines and analyze the effect of profitability, company size, and leverage of the good corporate governance, and the effect of good corporate governance of the earnings management on the companies listed on the Corporate Governance Perception Index. This study used purposive sampling method in sample selection, the criteria for a sample of the companies listed on the Corporate Governance Perception Index during the period 2013-2016. Based on these criteria, obtained a sample of 90 companies over a four-year observation period. Relations and or influence between variables and is described by using multiple regression analysis.The result showed that the profitability a not effect of the good corporate governance. Company Size a significant positive effect of the good corporate governance. Leverage a significant negative effect of the good corporate governance. Good Corporate Governance a significant positive effect of the earnings management.Keywords: Earnings Management, Good Corporate Governance, Profitability, Company Size, and Leverage..